Central American English - Holm, John A.; Escure, Geneviève (Varieties of English around the world. Text series, 1983)
This volume is about the Anglophone creoles to be found on the Caribbean coast of Central America (Belize, Honduras, Nicaragua, Costa Rica, Panama), and its offshore islands (Providencia, San Andrés and the Caymans) . The study of these Anglophone varieties is comparatively recent and based on current field work from Belize to Panama. One of the interesting features that emerges is the tentative map of diachronic and synchronic relationsships among the Anglophone creoles of the Caribbean, as illustrated partly by the lexicon and partly by grammatical constructions. The studies in this book are.